Public Management, TIC ́s and Development (2014)
The Information Technology and Communications (TIC) are synonymous for the contemporary world of transformation and change in the conception of life of individuals and the development of its activities; thus plays a vital role in achieving social objects. Its scope is given both in the private sector, which have recognized in advance the benefits they can provide, such as reducing costs and raising productivity levels, in terms of public sector institutions as they engine to achieve the purposes of the state in this process they have taken in hand to modernizing it and its institutions and aims at participatory inclusion of citizens who must feel a part of the state, which has a responsibility and a specific functions in front of him, thus participatory democracy develops. So the Colombia state recognizes and raises through the Ministry of Information Technologies and Communications, policies which foster care problem in technology, such as the reduction of the digital divide that is set as the gap between those who have access to digital technologies and those who do not; thus seeks to bring citizens to the government in compliance with the purposes of the institutions as providers of state services and promoting the Promotion of Transparency and Public Participation.